2019
DOI: 10.1002/14651858.cd010526.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Dental cavity liners for Class I and Class II resin-based composite restorations

Abstract: Eight studies, with over 700 participants, were included. Two studies were conducted in the USA, two in Thailand, two in Germany and one each in Saudi Arabia and Turkey. The studies compared the use of liners under tooth-colored resin fillings (RBC) in permanent teeth at the back of the mouth to no liners for Class I and Class II fillings. One of the two studies in the USA took place in dental practices, the others in university-based dental schools. All participants were over 15 years of age. Key results Very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…Resin composite restorations in the current study were placed directly in posterior teeth without the use of liners and bases in accordance with a systematic review [24] that linked the use of liners to the reduction in postoperative sensitivity, they revealed that there is an inconsistent evidence regarding the difference in POS between resin composite restorations placed with or without liners. Resin composite was placed using an incremental filling technique and indirect curing through the cusps, to minimize the deleterious effects of polymerization shrinkage stresses on the marginal integrity of the composite restorations as well as on the microscopic integrity of the adhesive bond to dentin [22].…”
Section: Discussionmentioning
confidence: 88%
“…Resin composite restorations in the current study were placed directly in posterior teeth without the use of liners and bases in accordance with a systematic review [24] that linked the use of liners to the reduction in postoperative sensitivity, they revealed that there is an inconsistent evidence regarding the difference in POS between resin composite restorations placed with or without liners. Resin composite was placed using an incremental filling technique and indirect curing through the cusps, to minimize the deleterious effects of polymerization shrinkage stresses on the marginal integrity of the composite restorations as well as on the microscopic integrity of the adhesive bond to dentin [22].…”
Section: Discussionmentioning
confidence: 88%
“…27,29 While there was a general preference among respondents of the current study to place a liner, a recent systematic review has shown that the evidence is inconsistent in terms of postoperative sensitivity with use of liners under resin-bonded restorations. 13 Another recent systematic review on whether calcium hydroxide liner is required for deep caries lesions confirmed these findings that treatment of the deep caries lesion is not a material-dependant technique. 30 This is also in line with the latest consensus recommendations which stated that there is no evidence to recommend a specific material.…”
Section: Discussionmentioning
confidence: 90%
“…[10][11][12] Furthermore, although traditional teaching advocates placement of a liner in deep caries lesions, particularly under metallic restorations such as amalgam, their role has recently been questioned. 13 The placement of a liner neither improves the longevity of the restoration 13 nor does it reduce the pulpal complications. 14 There is limited information on the attitudes and behaviour of Australian dentists to deep caries lesions.…”
Section: Australian Dental Journalmentioning
confidence: 99%
“…[45] Crown fracture *CP The condition in which diagnosis of crown fracture has been made by a dentist. [42] Ill-fitting prosthesis *CP The condition in which diagnosis of ill-fitting prosthesis has been made by a dentist. [42] Peri-implantitis *CP The condition in which diagnosis of peri-implantitis has been made by a dentist.…”
Section: Impaired Verbal Communicationmentioning
confidence: 99%
“…[42] Ill-fitting prosthesis *CP The condition in which diagnosis of ill-fitting prosthesis has been made by a dentist. [42] Peri-implantitis *CP The condition in which diagnosis of peri-implantitis has been made by a dentist. [46] Ill-fitting denture *CP The condition in which diagnosis of ill-fitting denture has been made by a dentist.…”
Section: Impaired Verbal Communicationmentioning
confidence: 99%